Vestibular neuronitis of idiopathi origin: a case report - Kola, Savitha; Janga, Akhila; Allam, Kartheek (International Journal of Research in Medical Sciences, 2021)
Vestibular Neuronitis is a neuronal condition characterized by spontaneous and unilateral vestibular loss suddenly with preserved hearing and no signs of brain stem dysfunction. According to large population studies, it is the sixth cause of vertigo with an incidence of 8%. Here is the case report of VN which was observed in a super speciality hospital. A 42 years old male patient was admitted in a private super speciality hospital with the chief complaints of history of vomiting 4 episodes, neck pain, mild headache and gaint imbalance since 5 days. Complete analysis of diagnostic reports was done and appropriate treatment given. This case emphasizes the importance of periodic evaluation and reporting of vestibular neuritis cases accumulating clinical knowledge. In this particular type of cases it is difficult to identify the etiology and pathophysiology, hence it is vitally important to conduct such studies.